Predictors of Frequent Recourse to Health Professionals by People With Severe Mental Disorders - Fleury, Marie-Josée (Can J Psychiatry, 2015)
OBJECTIVE: Based on Andersen’s behavioural model, our study sought to determine predictors and blocks of factors that could explain why people with severe mental disorders (SMDs) more often seek the services of health professionals. METHODS: This longitudinal study involved 292 users with SMDs located in Le Sud-Ouest, the southwest borough of Montreal. Data were collected from participants’ medical records and through 7 questionnaires. Using Andersen’s Behavioral Model of Health Services Use, independent variables were divided into 3 classes—predisposing factors, enabling factors, and need factors—and were introduced in this order in a hierarchical logistic model. RESULTS: Among 292 users, 110 (37.7%) were frequent users who consulted about one health professional every 3 days. Participants who were more likely to call on health professionals were single and older, depended on welfare as their main source of income, lived in supervised housing, suffered from schizophrenia, schizophrenia spectrum disorders, and adjustment disorders, and, marginally, exhibited multiple mental disorders. CONCLUSION: Mental health services could promote strategies to overcome the reluctance of younger people to seek professional services. Professionals should pay close attention to subsidiary conditions, such as adjustment disorders, from which people with SMDs may suffer. Interventions to improve the socioeconomic condition of unemployed people with SMDs may help to reduce health care service use among that clientele. Programs such as supported employment should be tailored and enhanced for people receiving welfare to decrease stigmatization and improve job market integration.